Social representations of sexual assistance services for people with physical disabilities in the context of Portugal - Pinho, A. R.; Carvalhaes, S.; Rodrigues, L.; Peixoto, M. M.; Oliveira, J. M. de.; Nogueira, C. (International Journal of Sexual Health, 2025)
Objectives The purpose of this study is to understand social representations of the Portuguese population regarding sexual assistance services for people with physical disabilities. Methods A questionnaire collected sociodemographic information and attitudes concerning sexual assistance from 167 Portuguese participants over 18 years of age. Results Results suggest most participants agree with legal recognition of sexual assistance services, expressing their agreement that it should require training, be remunerated, be aided by the availability of a list of professionals who provide these services, and attribution of public funds to make access possible to anyone. Contact with sex workers and perception of people with physical disabilities’ interest in sexual assistance are associated with higher acceptance of these services. Conclusions These findings showed positive social representations toward sexual assistance, emphasizing a need for further debate between people with disabilities, sex workers, academia and policymakers regarding training for providers of sexual assistance, creation of a list of sexual assistants, public funding to make these services accessible, and legal recognition of sexual services, to ensure the rights of people with disabilities and sex workers. Implications The findings underscore the importance of advancing public discourse on key issues related to sexual assistance, including the development of specialized training programs for sexual assistance, the establishment of a list of qualified sexual assistants, the provision of public funding to enhance service accessibility, and the legal recognition of sexual assistance. These measures are essential to safeguarding the rights of both people with disabilities and sex workers.